Perceived benefits of lifelong learning and the implications - Ang, Chooi Leng; Thi, Lip Sam; Pillai, Padmini; Hamzah, Abdul Rahman; Hussin, Zolkafli; Hanafi, Zahyah; Don, Mohd Sobri (2010)
This research attempts to examine the personal characteristics of lifelong learners and their motives behind pursuing lifelong learning. The research uses a cross-sectional data obtained from a sample of individual adult learners who are pursuing various lifelong learning programmes located at various regions of the country. A total of 767 usable questionnaires were returned for analysis. The findings from this study show that intrinsic benefits are the key drivers that motivate adult learners to participate in LLL. However, adult learners who are from younger age cohort (20-29 years old) and those who are not married had scored significantly higher extrinsic benefits. The results also show significantly difference for Chinese respondents who were found to have lower mean scores for both internal and external benefits compared to other ethnic groups.